Treatment Of Schizophrenia With Cobenfy (KarXT): A Literature Review - Laura Kurczoba; Karolina Skonieczna; Magdalena Badziąg; Paulina Szulc; Martyna Kłossowska; Olimpia Wiciun; Olga Kądziołka; Kacper Ordon (Quality in Sport)
Introduction and purpose: In September 2024, the FDA approved a new drug for the treatment of schizophrenia in adults, Cobenfy, also known as KarXT. COBENFY combines xanomeline, a muscarinic agonist, and trospium chloride, a muscarinic antagonist. It is the first antipsychotic approved for the treatment of schizophrenia that targets cholinergic receptors rather than dopamine receptors, which could be a completely new standard of care. The purpose of this literature review is to introduce the new psychotropic drug, discuss the mechanism of action, and present the results of the EMERGENT-1, EMERGENT-2 and EMERGENT-3 clinical trials.